Edukasi Tentang Perawatan Payudara Ibu Hamil Untuk Meningkatkan Produksi Asi Ibu Di Wilayah Kerja Puskesmas Bantimurung - Djunaedi, Djunaedi; Nursiah, Andi; Idris, Idris; Fitri, Lidia (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2023)
Breastfeeding is one of the best investments for survival and improving health, socio-economic development of individuals and nations. This coverage cannot be separated from problems that occur during the breastfeeding process, including the false belief that little milk comes out or that breast milk is not sufficient for the baby's needs. This situation is caused by several factors, including the mother's psychological condition, abnormal breast shape, baby sucking, which can affect breast milk production. Various studies have been carried out to facilitate breast milk production, including the Oxytocin Massage method, Marmet Technique, Rolling Massage (back), Endorphin massage, Breast Care, but due to limited information in health services regarding implementation procedures, these methods are only known but rarely given by health workers as care givers to patients. The service is carried out with the aim of providing knowledge to mothers and the community about Endorphine Massage in Increasing Breast Milk Production. The method used in community service begins with giving a pre-test, delivering material, evaluating with a post-test and practice. The target audience is pregnant women and breastfeeding mothers at the Bantimurung Community Health Center. The result of this community service was that 71.4% of participants' knowledge increased about Endorphine Massage in Increasing Breast Milk Production. This was proven by the enthusiasm of the participants who actively asked questions, discussed and shared breastfeeding experiences. After this activity takes place, there needs to be follow-up from the participants to apply the counseling that has been given.